Art and crafts - Selim, Lala Rukh.; Cultural Survey of Bangladesh Project (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; translated from Bengali.
Includes bibliographical references and index.
Includes translations from Bengali.
Keywords: Art, Bangladeshi; Art, Indic -- India -- Bengal; Folk art -- Bangladesh; Decorative arts -- Bangladesh